Efficacy of a rhythmic gymnastics-specific injury prevention program: An assessor-blinded cluster-randomized controlled trial - Gram, M. C. D.; Fagerland, M. W.; Bø, K. (Scandinavian Journal of Medicine & Science in Sports, 2025)
Overuse injuries are common among competitive rhythmic gymnasts, with an estimated weekly prevalence of 37% and with the knees, lower back, and hip/groin as the most common injury locations. Reduced physical capacity (e.g., strength and flexibility) has been hypothesized to contribute to the high prevalence of overuse injuries. The primary objective of this trial was to assess if exercises targeting reduced physical capacity in the knees, lower back, and hip/groin reduce the prevalence of overuse injuries compared with usual training. Twenty-three rhythmic gymnastics clubs were cluster-randomized to an intervention group (IG: 12 clubs and 119 gymnasts) and a control group (CG: 11 clubs and 86 gymnasts). Included gymnasts had to be = 12 years of age and training = 3 days per week. The IG performed a targeted injury prevention program (IPP) during training/warm-up for 8 months (November 2022 to June 2023). The CG performed usual training. The prevalence of overuse injuries in the targeted locations was measured monthly in both groups using the Oslo Sports Trauma Research Centre Questionnaire on Health Problems (OSTRC-H2). The response rate to OSTRC-H2 was 94%. There was no difference in the prevalence of overuse injuries in the targeted locations between the two groups; odds ratio = 0.86 (95% CI 0.32 to 2.29); p = 0.77 for intervention vs. control. The results suggest that a targeted IPP alone is not enough to prevent overuse injuries in the knees, lower back, and hip/groin among competitive rhythmic gymnasts. Other measures (e.g., load management and proper training planning) might be targeted in future studies.